Viabilidade econômica da produção de biogás em granjas de suínos, por meio da análise de séries temporais - Rockenbach, Felipe Luis (2014)
This study aims to gather, analyze, and interpret the potential and economic feasibility of sequestering carbon dioxide and/or generating renewable energy from the processing of pig manure, via time series analysis, using the Box and Jenkins (1970) models for future prediction. Swine production systems generate large amounts of waste which are highly polluting and impact the environment, principally greenhouse gases. When treated, these gases produce methane gas and in turn biogas, which when removed correctly is converted into electricity and carbon credits, leaving behind a high quality biofertilizer. This scenario of carbon dioxide sequestration was only possible after the adoption of the Kyoto Protocol, which provides for the Clean Development Mechanism (CDM) and the sale of Certified Emission Reductions (CER); electrical energy was affected by Regulatory Resolution 482/ 2012 of the National Electric Energy Agency (ANEEL). Data were was gathered with the support of the Municipal Association of Swine Producers of Toledo (AMST) and the BRF Company. This study demonstrates that it is feasible to use biogas and that the payback period follows a production scale with equipment operating 10 hours or more daily. Consequently, the payback period will be between 70 and 80 months, with production of electrical energy and/or in conjunction with the production of carbon credits. The study also shows that the production volume is feasible and should accommodate a minimum number of pigs. In addition, prediction models are important tools since they anticipate the behavior of the series under study, providing support so that investments can be made, reducing risks to the both the swine producer (in the area of finances) and to the farm, as well as allowing for another source of income. By reducing production costs, autonomy is guaranteed in ensuring an uninterrupted supply of electricity, which is needed for swine operations which become more and more dependent on technology.